Rainfall Infiltration under Various Building Layouts Using Concrete Microseepage Wells - Xiaolan Liu; Shunqun Li; Yunfeng Bai (Advances in Materials Science and Engineering)
Low-impact development measures are a kind of ecological technology system that can easily realize urban rainwater collection and utilization to alleviate the contradiction between flooding/water logging disasters and water shortages. But most of the low-impact development measures are difficult to solve the problem of deep soil infiltration and fully utilize runoff regulation and seepage benefits. Therefore, this paper proposes the concrete microseepage well with the optimum proportion of crushed stone, cement, and water of 1 : 0.13 : 0.11 and 2% steel fiber content. The artificial rainfall experiment is applied to verify the high-infiltration of concrete microseepage well in deep soil. The numerical analysis shows that the concrete microseepage well around a single building and two adjacent buildings can all decrease 15%–40% of the pore water pressure, decrease 11%–33% of total head, and improve 43–55 times of infiltration velocity. The concrete microseepage well with 0.1 m in diameter and 1 m in height can affect the infiltration area of 1 m2. Each building being surrounded by seepage wells is the optimal layout scheme to alleviate the flooding/water logging disasters. This study provides a scientific reference for the development of sponge cities with low-impact development measures to reduce the problem of flooding/water logging disasters and water shortages.